Developing Program Leader Networks and Resources to Enhance Learning and Teaching in Multicampus Universities : Final Report LE8-810. - Krause, Kerri-Lee; Scott, Geoff; Campbell, Stuart; Lizzio, Alf; Spencer, David; Bath, Debra; Clark, Jo-Anne (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a project that developed an online, modularised good practice guide for program leaders, along with resources for policy-makers and those who induct and support program leaders. Program leader networks were consolidated in participating universities, yielding good practice models. Regional forums shared good practices for supporting and developing program leaders. This project builds on the Scott et al ALTC project's recommendations and complements the UTas multicampus project, focusing on the role of Program leader. It analyses the experiences of a sample of 24 experienced and early career program leaders across a range of undergraduate and postgraduate disciplinary programs in three multicampus universities. The project's three phases were: 1: Project establishment and program leader recruitment, liaising with project reference group (with UTas project), and with international experts. 2: Develop program leader communities through network meetings, document experiences, attitudes and interactions of 24 program leaders through interviews, self-reporting and network meetings, interview institutional leaders and policy-makers at department and university level to identify policy implications, online resource development, joint workshop, formative evaluation. Data collection will yield models of good practice in mentoring and network development, along with implications for effective policy-making. 3: Disseminate findings, including four regional forums, summative evaluation.